2023
DOI: 10.1111/dom.14990
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of semaglutide across the SUSTAIN and PIONEER phase IIIa clinical trial programmes

Abstract: Aim Glucagon‐like peptide‐1 receptor agonists improve glycaemic control: some are now available as oral and subcutaneous formulations, and some have indications for reducing cardiovascular risk. The expanded scope for these therapies warrants comprehensive safety evaluations. We report the safety/tolerability of subcutaneous and oral semaglutide from the SUSTAIN and PIONEER clinical trial programmes, respectively. Materials and methods Adverse events (AEs) from 16 randomized placebo‐ or active‐controlled phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…In the SUSTAIN randomized controlled trials (RCT), semaglutide, a once‐weekly human GLP‐1 analogue, was associated with superior, clinically relevant improvements in glycaemic control (mean reduction in HbA1c of up to 1.8% point across the trials) and body weight (mean reduction across the trials of up to 6.5 kg) versus placebo or active comparators 15‐24 . The safety profile of semaglutide was similar to that of other GLP‐1RAs, in particular, gastrointestinal adverse events (AEs), which were most frequently non‐serious nausea, diarrhoea and vomiting 15‐25 . Semaglutide is reimbursed in France for the treatment of insufficiently controlled T2D, as dual therapy in combination with metformin and as triple therapy in combination with metformin and a sulphonylurea 26…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the SUSTAIN randomized controlled trials (RCT), semaglutide, a once‐weekly human GLP‐1 analogue, was associated with superior, clinically relevant improvements in glycaemic control (mean reduction in HbA1c of up to 1.8% point across the trials) and body weight (mean reduction across the trials of up to 6.5 kg) versus placebo or active comparators 15‐24 . The safety profile of semaglutide was similar to that of other GLP‐1RAs, in particular, gastrointestinal adverse events (AEs), which were most frequently non‐serious nausea, diarrhoea and vomiting 15‐25 . Semaglutide is reimbursed in France for the treatment of insufficiently controlled T2D, as dual therapy in combination with metformin and as triple therapy in combination with metformin and a sulphonylurea 26…”
Section: Introductionmentioning
confidence: 98%
“…[15][16][17][18][19][20][21][22][23][24] The safety profile of semaglutide was similar to that of other GLP-1RAs, in particular, gastrointestinal adverse events (AEs), which were most frequently non-serious nausea, diarrhoea and vomiting. [15][16][17][18][19][20][21][22][23][24][25] Semaglutide is reimbursed in France for the treatment of insufficiently controlled T2D, as dual therapy in combination with metformin and as triple therapy in combination with metformin and a sulphonylurea. 26 The SURE programme comprises nine non-interventional, singlearm, observational studies across 10 countries investigating onceweekly semaglutide in a diverse range of patients with T2D in a real-world setting.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the promising effects of SGLT2 inhibitors in HFpEF patients 5 and the impressive effects of GLP-1 agonists on symptom burden in obese HFpEF 64 , more treatment options are warranted for this highly prevalent and morbid disorder, especially considering the limited tolerability to GLP-1 agonists 65 . With a positive safety and tolerability profile, NO 2 -OA emerges as a potentially important drug for treating HFpEF and other cardiopulmonary diseases 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Long term studies of liraglutide in rodents and primates have not revealed increased pancreatitis risk ( 48 50 ). Moreover, systematic reviews and meta-analyses of randomised controlled trials have not shown increased incidence of pancreatitis in patients with type 2 diabetes treated with liraglutide, exenatide or semaglutide ( 51 53 ). Appropriate monitoring will be necessary for GLP-1R agonists use in the treatment of patients with lipodystrophy.…”
Section: Discussionmentioning
confidence: 99%